Determinan Keputusan Mahasiswa Dalam Memilih Karir Pada Bidang Perpajakan - Catur Dewi, Caroline; Oktavini, Eva (LPPM UBP, 2024)
This research was conducted with the aim of determining whether the influence of perception, motivation, and tax knowledge affects students' decisions to pursue a career in taxation. The research model involved conducting a survey using an online questionnaire through Google Forms. The sample was determined using purposive sampling method with criteria of students in the 3rd, 5th, and 7th semesters of the accounting and management programs at Krida Wacana Christian University. The research data were analyzed using multiple linear regression analysis to examine the influence of independent variables on the dependent variable. The results of this study indicate that perception, motivation, and tax knowledge have a positive influence on students' decisions to pursue a career in taxation.